Taking a broader view of things: towards a transdisciplinary approach to cancer - Rauch, Cyril; Blott, Sarah; Stewart, Simon (Sapienza, Universita di Roma, 2017)
Cancer is widely considered an abnormality that emerges from within the body and which must be destroyed and defeated. But we still do not know precisely how and why cancer starts, and while a ‘magic bullet’ cure has failed to materialise, those adopting a more pragmatic stance are increasingly arguing that if we cannot eradicate all cancer cells, we should look instead towards a ‘stalemate’ and find ways of managing cancer as a chronic disease. This article seeks to extend the reach of research in this field by taking a broader view and working towards a transdisciplinary approach in order to better understand cancer. First, we draw attention to obstacles that hinder progress in formulating new perspectives on cancer. Second, we ask why the genocentric approach to cancer remains dominant. One explanation is the legacy of Cartesian thinking. Third, we consider new ways of conceptualizing cancer so that it is not only a scientific object but also an object of life that has a framed existence within the body as part of a wider process of biological evolution. We draw on two key examples which highlight the importance of adopting a transdisciplinary approach: multi-drug resistance and cancer genomics.